Elevated serum IL-39 in patients with ST-segment elevation myocardial infarction was related with left ventricular systolic dysfunction. (June 2017) - Luo, Yu; Liu, Feng; Liu, Huadong; Chen, Hongdan; Cheng, Wenfei; Dong, Shaohong; Xiong, Wei
Aim: To investigate the changes and significance of circulating IL-39 in patients with acute coronary syndrome (ACS).Patients & methods: Serum IL-39 levels in ACS patients and normal coronary arteries were measured. The correlations of IL-39 with high-sensitivity CRP, cTnI, N-terminal of the prohormone brain natriuretic peptide (NTproBNP) and left ventricular ejection fraction were investigated.Results: The serum levels of IL-39 in ACS patients were significantly increased. IL-39 levels were positively correlated with NTproBNP, high-sensitivity CRP and cTnI, negatively correlated with left ventricular ejection fraction in ACS patients. The most significant correlation arose between serum IL-39 and NTproBNP in STEMI patients (r = 0.8309; p < 0.0001).Conclusion: Circulating level of IL-39 might be a predictor of cardiac systolic dysfunction in ST-segment elevation myocardial infarction patients.